Sosialisasi Penggunaan Marketplace Tokopurwakarta.Com Kepada UMKM Di Desa Benteng Kecamatan Campaka Kab. Purwakarta - Tripramudi, Agung; Jalaludin, Jalaludin; Sucipto, Moch. Cahyo; Fauzi, Toni Arif (ADINDAMAS: Jurnal Pengabdian Kepada Masyarakat, 2021)
Based on the observation that sales of MSMEs and the community in Benteng Village have not been optimal, residents hope that with the introduction of an application or marketplace, it will be able to increase the number of sales so that it has an impact on increasing the profits obtained from sales. Currently, residents still do not have knowledge about the Tokopurwakarta.com or Topur marketplace which can be used as a means of supporting online sales promotions. Through this community service program, the PKM team helps residents provide the necessary education and information to assist in the process of creating marketplace accounts for residents. The purpose of this community service program is to socialize the use of the tokopurwakarta.com marketplace to MSMEs in Benteng Village, Campaka District, Kab. Purwakarta. This Community Service activity that has been carried out can be concluded that the process of socializing the use of the tokopurwakarta.com marketplace from the beginning to the final stage is evidenced by the increased trust of MSME actors in marketing their selling products, and for the public to increase knowledge about online transactions on the tokopurwakarta marketplace. com.